Comparison of Outcomes and Recurrence in Chronic Subdural Hematoma Patients Treated by Burr-Hole Drainage with or without Irrigation - Jongwook Choi; Kum Whang; Sungmin Cho; Jongyeon Kim (Journal of Trauma and Injury)
Purpose Chronic subdural hematoma (CSDH) is a common disease in elderly patients and is usually treated by burr-hole drainage. However, the optimal surgical technique for treating CSDH has not been determined. In this study, we analyzed outcomes and recurrence rates after burr-hole drainage with or without irrigation in patients with CSDH. Methods Eighty-two CSDH patients treated with burr-hole drainage at Wonju Severance Christian Hospital from March 2015 to June 2016 were enrolled in this study. The subjects were divided into three groups based on the surgical technique performed as follows: single burr-hole drainage without irrigation (group A, n=47), single burr-hole drainage with irrigation (group B, n=14), or double burr-hole drainage with irrigation (group C, n=21). These three groups were compared with respect to clinical and radiological factors and the recurrence rate, and independent factors predicting recurrence were sought. Results After burr-hole drainage, CSDH recurred in 15 (18.3%) of the 82 patients, and six patients (7.3%) required reoperation. More specifically, recurrence was observed in 12 patients (25.5%) in group A, one (7.1%) in group B, and two (9.5%) in group C. The number of burr-holes did not significantly affect recurrence (odds ratio [OR]=0.38; 95% confidence interval [CI]: 0.60–2.38), but irrigation had a significant effect (OR=0.20; 95% CI: 0.04–0.97). Conclusions This study shows that irrigation during burr-hole surgery in CSDH patients significantly reduced the risk of recurrence, regardless of the number of burrholes used. We therefore recommend the use of active irrigation during burr-hole drainage surgery in CSDH patients.